Proposta para o cálculo de carga de ruptura por punção em lajes de concreto reforçado com fibras de aço - Dantas, Lucas Guedes (2020)
This work proposes an adjustment function in the rupture load formulation of flat concrete slabs without shear reinforcement under puncture according to standard NBR 6118:2014, which takes into account the influence of the fiber content. For the definition of the adjustment function, data from 119 reinforced concrete and steel fiber-reinforced concrete (SFRC) plates supported on their edges and tested under concentric load applied in a square section are used, simulating the connection of slab and column. The adjustment function is defined with the fiber content parameters and the k coefficient (depending on the concrete compressive strength class). The application of the adjustment function in experimental results (slabs with fibers) shows an average ratio of 1.29 between the experimental rupture load and the adjusted load. A relationship of the same magnitude (1.29) is observed between the experimental rupture load (slabs without fibers) and the load calculated according to NBR 6118: 2014.